God’s Attributes in Early Qur’anic Exegesis between Text and Context: A Case Study of Muqātil b. Sulaymān al-Balkhī’s Tafsīr - Mabrouk Chibani Mansouri; Shareefa Bint Salim Aal-Said‎; Abdulla Ibn Salim Al-hinaei‎ (UIN Sunan Kalijaga Yogyakarta, 2026)
This article examines debates over the khabarī (scriptural) divine attributes in early Qur’anic exegesis through a case study of Muqātil b. Sulaymān al-Balkhī (d. 150/767). Framed by the analytical dyad of text and context, it asks how anthropomorphic and corporealist readings emerged in the first/early second century AH and what cultural matrices shaped them. Methodologically, the study combines a historical‑inductive reading of Muqātil’s tafsīr in its primary textual witnesses, a deconstructive analysis of his interpretive system, and a critical analytical comparison of selected motifs—corporeality, istiwāʾ as “sitting,” the throne and its bearers, the kursī, and the Adam creation narrative. The findings suggest that literalist anthropomorphic exegesis crystallized in the multilingual eastern Islamic lands, especially Khurāsān/Central Asia, where local religious traditions and “Eastern” theological imaginaries plausibly informed the reception of Qur’anic descriptions of God; this influence is advanced as a text and context based hypothesis rather than a claim of demonstrable direct borrowing. The article also maps early scholarly critiques that problematized Muqātil’s approach in tafsīr and ḥadīth. By foregrounding intertextuality and acculturation, the study offers a methodological pathway for linking early exegetical discourse to its socio‑cultural environments and reassessing the genealogy of anthropomorphism in formative tafsīr.